A successful pregnancy outcome after surgical treatment for a bicornuate uterus. Case report - Аlfiya G. Yashchuk (IP Berlin A.V., 2021)
This article presents a clinical case in a woman with a full two-legged uterus. This pathology in the patient was revealed by ultrasound examination in 2013. There is one spontaneous miscarriage in the anamnesis; later, the patient did not become pregnant with regular sexual activity without contraception. A comprehensive examination of the patient was carried out. It was decided to conduct a hysteroscopy, during which one cervical canal was identified, in the area of the internal pharynx, a division into two hemipolostas was visualized. In the future, the patient underwent Strassmanns reconstructive plastic surgery, which is the gold standard for this pathology. Laparatomic metroplasty is a safe and effective procedure for women with a bicornuate uterine malformation. The postoperative period was uneventful. A year later, the patient became pregnant in the natural cycle. Pregnancy proceeded without complications, culminating in the birth of a healthy child.